On the origins of the BIS macro-prudential approach to financial stability: Alexandre Lamfalussy and financial fragility - Ivo Maes (National Bank of Belgium, 2009)
Among the international policy institutions, the Bank for International Settlements (BIS) is known for its sensitivity to financial stability issues. Attention to the "macro-prudential" dimension of financial stability is very typical for the BIS. The Bank's macro-prudential approach first came to the fore in the 1986 Cross Report. It defined the macro-prudential domain as "the safety and soundness of the broad financial system and payments mechanism". In this paper, it will be argued that Alexandre Lamfalussy, who was at the BIS from 1976 to 1993, played a crucial role in shaping the Bank's approach to financial stability. Lamfalussy is renowned for taking a broad macroeconomic view and for focusing on the systemically important financial institutions, as the failure of one of these individual institutions would threaten the whole financial system. In Lamfalussy's view, there is thus very much an overlap between the micro- and macro-prudential dimensions of financial stability. This paper traces Lamfalussy's analysis of financial fragility and goes into the reasons for his sensitivity to it. Among the main elements involved were: a "Keynesian" Weltanschauung (that a market economy is not sufficiently self-correcting); the emphasis of Dupriez (his teacher in Louvain) on cycles; Lamfalussy's own experience as a commercial banker; BIS involvement in financial stability issues, especially the Latin American debt crisis of 1982-83; and research in the central banking community on financial innovations in the early 1980s
Keywords: A11; B22; B32; E3; F02; G10; N10; 330; Lamfalussy; BIS; macro-prudential; systemic stability; financial fragility; risk; Finanzsektor; Finanzkrise; Finanzprodukt; Makroökonomik; Keynesianismus